Retained interests in securitisations and implications for bank solvency - Anna Sarkisyan; Barbara Casu (European Central Bank (ECB), 2013)
Using US bank holding company data for the period 2001 to 2007, this paper examines the relationship between banks' retained interests in securitisations and insolvency risk. We find that the provision of credit enhancements and guarantees significantly increases bank insolvency risk, albeit this varies for different levels of securitisation outstanding. Specifically, retained interests increase insolvency risk for “large-scale” securitisers while having a risk-reducing effect for “small-scale” and/or first-time securitisers. In addition, we find that the type of facility provided has implications for bank risk, with those with the most subordinated (first-loss) position having the greater impact on banks' default risk. Finally, we find that engagement in third-party securitisations has no significant effect on bank risk.
Keywords: G21; G32; 330; insolvency risk; retained interests; securitisation